2021
DOI: 10.1021/acs.jnatprod.1c00480
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Betulonic Acid by the Fungus Rhizopus arrhizus CGMCC 3.868 and Antineuroinflammatory Activity of the Biotransformation Products

Abstract: Biotransformation of betulonic acid (1) by Rhizopus arrhizus CGMCC 3.868 resulted in the production of 16 new (3, 5, 6, and 9–21) and five known compounds. Structures of the new compounds were established by analysis of spectroscopic data. Hydroxylation, acetylation, oxygenation, glycosylation, and addition reactions involved the C-20–C-29 double bond. Antineuroinflammatory activities of the obtained compounds in NO production were tested in lipopolysaccharides-induced BV-2 cells. Compared with the substrate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…10−14 For example, a rearranged product of curcumenol by a fungal strain Mucor polymorphosporus AS 3.3443 showed more potent anti-inflammatory activity than the original compound, 10 curcumenol, and hydroxylation of betulonic acid by a fungal strain Rhizopus arrhizus CGMCC 3.868 exhibited enhanced anti-inflammatory activity. 11 Recently, several studies have shown that gut bacteria can metabolize clinical drugs modifying their chemical structure and potentially their bioavailability. 15−17 We herein describe the application of the bioactivity-HiTES method to C. matruchotii KCTC 19325 isolated from human dental plaque to discover new antibacterial metabolites.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10−14 For example, a rearranged product of curcumenol by a fungal strain Mucor polymorphosporus AS 3.3443 showed more potent anti-inflammatory activity than the original compound, 10 curcumenol, and hydroxylation of betulonic acid by a fungal strain Rhizopus arrhizus CGMCC 3.868 exhibited enhanced anti-inflammatory activity. 11 Recently, several studies have shown that gut bacteria can metabolize clinical drugs modifying their chemical structure and potentially their bioavailability. 15−17 We herein describe the application of the bioactivity-HiTES method to C. matruchotii KCTC 19325 isolated from human dental plaque to discover new antibacterial metabolites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Biotransformation is an alternative and useful method for enhancing the structural diversity of small molecules, potentially leading to increased bioactivity. Bacteria or fungi can cause diversification of natural product structures by hydroxylation, acetylation, oxygenation, glycosylation, rearrangement, and others. For example, a rearranged product of curcumenol by a fungal strain Mucor polymorphosporus AS 3.3443 showed more potent anti-inflammatory activity than the original compound, curcumenol, and hydroxylation of betulonic acid by a fungal strain Rhizopus arrhizus CGMCC 3.868 exhibited enhanced anti-inflammatory activity . Recently, several studies have shown that gut bacteria can metabolize clinical drugs modifying their chemical structure and potentially their bioavailability. …”
Section: Introductionmentioning
confidence: 99%
“… 1 Furthermore, organoselenium compounds have emerged as valuable building blocks in organic synthesis and are employed as radicals, electrophiles and nucleophiles to construct a wide range of chemical bonds. 2 Specifically, seleno-substituted heterocycles and vicinally functionalized selenides are highly notable due to their significance as chemical reagents, building blocks, and biologically active molecules ( Scheme 1 ). 3 Hence, numerous attempts have been made to develop a synthetic route for accessing these compounds.…”
Section: Introductionmentioning
confidence: 99%